How to screen frailty in outpatients with heart failure: multimodality assessment vs. the Vulnerable Elderly Survey 13 (VES-13) scale. (3rd October 2022) - Roig, T; Gonzalez, B; Lopez, Y; Rivas, C; Arderiu, A; Pulido, A; Crespo, E; Velayos, P; Diaz, V; Altabella, M; Bares, D; Barcelo, E; et al.
Abstract: Background: During two decades we have been screening fragility in outpatients with heart failure (HF) with a multimodality assessment using several geriatric scales, showing that frailty or fragility is frequent in HF patients, even in young patients, and we demonstrated that this identified fragility played an important prognostic role. Frailty is a medical syndrome with multiple causes and contributors that increases outpatients' vulnerability so a minimal stress can cause functional impairment, with a major risk of dependency, even death. Frailty can be reversible or attenuated by interventions. Nowadays several specific scales for fragility or frailty detection are widely available. One of them, the Vulnerable Elderly Survey 13 (VES-13) has scarcely been used in HF. Purpose: To assess the prevalence of fragility in an outpatient HF Clinic at first visit using both the VES-13 scale and a multimodality assessment that includes Barthel index, OARS scale, Pfeiffer test, and abbreviated Yesavage Geriatric Depression Scale of 4 items (GDS), and compare the two approaches Methods: Nurses fulfilled the scales with the patients at their first visit. An scoring ≥3 in the VES-13 scale and the presence of one of the predefined criteria in the multimodality assessment (Barthel <90; OARS score <10 in women and <6 in men; Pfeiffer Test score >3±1, depending on educational level; one positive depression response in abbreviated GDS; and age >85 years or nobody to turn to for help) were considered to have fragility for the purpose of the study. Results: From March 2021 to December 2021, 136 patients were evaluated with the two fragility screening modalities (mean age 68.8±10.8 years, 64% men, 46% from ischaemic aetiology, 65.4%/27.9% in NYHA class II/III, LVEF 39.5% ± 13.4). VES-13 identified 51 (37.5%) patients with fragility, while the multimodality assessment detected 45 (33.6%) patients. Barthel index and depressive symptoms in the GDS were the most altered items (19 and 20 patients respectively) in the multimodality assessment. Concordance between VES-13 and multimodality assessment was 83.8%, but Cohen's Kappa was 0.65, not reaching the suitable level of 0.70. Conclusions: VES-13 was capable of identifying a higher number of patients with fragility at first visit in the routine screening performed in an outpatient HF clinic, than the multimodality assessment used in the last decades. Follow-up of patients and further analysis will allow evaluating which of these two approaches adds more value for outcomes prediction. Funding Acknowledgement: Type of funding sources: None.